Influence of Boycott, Price, and Product Quality on Consumer Decisions for Unilever Sanitation Product in Pontianak - Lestari Lestari; Nur Aini Anisa; Komarun Zaman (CV. Ulil Albab Corp, 2025)
This study aims to examine the extent to which boycott actions, price, and product quality influence consumer purchase decisions regarding Unilever’s sanitation products in Pontianak. A quantitative approach was employed, and data were collected using questionnaires distributed to 100 respondents selected through purposive sampling. The data were analyzed using multiple linear regression, t-tests, and F-tests. The findings indicate that both consumer boycott and price do not have a significant impact on purchase decisions. In contrast, product quality has a positive and statistically significant effect (β = 0.382; sig. = 0.029). The constant value of 33.611 suggests that even when all independent variables are assumed to have no effect, the purchase decision level remains high. The R square value of 0.072 indicates that the three variables together explain only 7.2% of the variance in purchase decisions. The F-test result of 1.856 with a significance level above 0.05 confirms that the independent variables do not have a simultaneous effect. These findings highlight that product quality remains the dominant factor influencing purchase decisions, even amid social issues such as boycott movements.